Assessing constraints to agricultural development in circumpolar Canada through an innovation systems lens. (December 2021) - Seguin, Rose; Lefsrud, Mark G.; Delormier, Treena; Adamowski, Jan
Abstract: CONTEXT: The circumpolar region of Canada experiences high rates of food insecurity due to the harsh climate and terrain and limited infrastructural capacity restricting local production and environmental changes impacting traditional food systems. As such, the region heavily relies on imported commodities which are expensive and of low nutritional quality. Agricultural development has the potential to mitigate circumpolar food insecurity and is underway to various degrees throughout the region, forming a complex and emerging agricultural system. OBJECTIVE: Using a rapid appraisal of agricultural innovation systems (RAAIS) approach, we studied the status of agricultural development across circumpolar Canada, e.g., Yukon, the Northwest Territories, Nunavut, Nunavik (Quebec) and Nunatsiavut (Newfoundland and Labrador). METHODS: Forty semi-structured interviews regarding constraints to agricultural development in circumpolar regions were conducted with stakeholders belonging to one or more of the following groups: farmers, government, private sector, non-governmental organizations and individuals in the fields of research and training. Constraints were labeled with a descriptive code, then sorted according to dimensions (biophysical, economic, institutional, political, sociocultural or technological) and structural conditions for innovation. The frequency of each constraint was calculated to determine the weight of constraints by subregion. RESULTS AND CONCLUSIONS: Constraints varied between subregions, indicating that innovations should be subregion-specific and co-developed with local communities to ensure their success and longevity. Circumpolar agriculture was found to be most greatly restricted by economic barriers such as limited capital cost recovery, community buy-in, high operating costs and funding options. Among the four structural conditions for innovation used in RAAIS, constraints were somewhat equally distributed between capabilities and resources, infrastructure and assets, and institutions. At the time the study was undertaken, interaction and collaborations were less restrictive to agricultural development. Suggested strategies for facilitating agricultural development included financial incentives, agricultural training programs, and infrastructure development. SIGNIFICANCE: To the authors' knowledge, this study is the first to apply AIS approaches to an emergent agricultural system and does so over a large and diverse region. The RAAIS approach effectively identified the numerous constraints to circumpolar agriculture, although the methodology did not account for the interconnectedness of constraints and resultant blocking mechanisms. Future research would benefit from combining AIS approaches with structural-functional analyses to mitigate these constraints and blocking mechanisms. Graphical abstract: Unlabelled Image Highlights: Agricultural development in circumpolar Canada was most restricted by economic constraints Prevalence of particular constraints varies between subregions, owing to environmental and sociocultural conditions Agricultural development is restricted by lack of power among stakeholders Circumpolar agriculture requires a holistic approach thus is well suited to innovation systems approaches